2019
DOI: 10.1177/0145561319871240
|View full text |Cite
|
Sign up to set email alerts
|

Can Pregnancy Lead to Changes in Hearing Threshold?

Abstract: Purpose: This study explores the changes in hearing thresholds in pregnancy. Materials and Methods: A prospective hospital-based observational study was performed with a total of 69 patients in the age-group of 18 to 40 years. Patients underwent hearing assessment twice during the study period. Conventional pure tone audiometry and impedance audiometry were performed, first during the antepartum period (28-32 weeks of gestational age) and second time during the postpartum period (6 weeks postpartum). Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This observation is consistent with other authors. Kwatra et al [33] also reported that in their study, a significant difference was seen between the average of air conduction threshold values in speech frequencies when antepartum values were compared with postpartum values.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This observation is consistent with other authors. Kwatra et al [33] also reported that in their study, a significant difference was seen between the average of air conduction threshold values in speech frequencies when antepartum values were compared with postpartum values.…”
Section: Discussionmentioning
confidence: 73%
“…The results obtained by some authors [15,33], showed that there is a decrease in low frequency hearing level during pregnancy, similar to Meniere disease, but in pregnancy, the values remain within normal limits. The cause of the abovementioned change can be due to salt and water retention, which is seen during pregnancy.…”
Section: Discussionmentioning
confidence: 88%